Identification of HLA-A2 restricted T-cell epitopes within the conserved region of the immunoglobulin G heavy-chain in patients with multiple myeloma - Belle, Sebastian; Fang, Han; Condomines, Maud; Christensen, Olaf; Witzens-Harig, Mathias; Kasper, Bernd; Kleist, Christian; Terness, Peter; Moos, Marion; Cremer, Friedrich Walter; Hose, Dirk; Ho, Anthony Dick; et al. (European journal of haematology, 2008)
Objective: The aim of this study is the identification of HLA-A2 restricted T-cell epitopes in the conserved region of the immunoglobulin-G-heavy-chain (IgGH) that can be used for immunotherapy in multiple myeloma (MM) patients. Methods: After the IgGH gene sequence was scanned for HLA-A2 restricted T-cell epitopes with a high binding affinity to the MHC-I-complex, promising nona-peptides were synthesized. Peptide specific CD8 + T-cells were generated from peripheral blood mononuclear cells (PBMC) of healthy donors (HD) and patients with MM using peptide pulsed dendritic cells (DC) in vitro. The activation and cytotoxicity of CD8 + T-cells was analyzed by IFN-α ELISpot-assay and 51Chromium release-assay. HLA-A2 restriction was proven by blocking T-cell activation with anti-HLA-A2 antibodies. Results: Two HLA-A2 restricted T-cell epitopes-TLVTVSSAS derived from the IgGH-framework-region 4 (FR4) and LMISRTPEV from the constant region (CR)-induced expansion of specific CD8 + T-cells from PBMC in two of three (TLVTVSSAS) and one of three (LMISRTPEV) HD respectively. Specific T-cells were induced from PBMC in two of six (TLVTVSSAS) and eight of 19 (LMISRTPEV) patients with MM. Specific CD8 + T-cells also lysed peptide-pulsed target cells in 51Chromium release-assay. LMISRTPEV specific CD8 + T-cells from MM patients lysed specifically the HLA-A2 + IgG myeloma cell line XG-6. Conclusion: We identified two HLA-A2 restricted T-cell epitopes-TLVTVSSAS and LMISRTPEV-which can yield an expansion of CD8 + T-cells with the ability to kill peptide-loaded target cells and HLA-A2 + IgG+ myeloma cells. We conclude that TLVTVSSAS and LMISRTPEV could be T-cell epitopes for immunotherapy in MM patients.